2011
DOI: 10.1161/circep.110.961771
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine-Independent Heart Rate Increases Require Ca 2+ /Calmodulin-Dependent Protein Kinase II

Abstract: Background Catecholamines increase heart rate by augmenting the cAMP responsive HCN4 ‘pacemaker current’ (If) and/or by promoting inward Na+/Ca2+ exchanger current (INCX), by a ‘Ca2+ clock’ mechanism in sinoatrial nodal cells (SANCs). The importance, identity and function of signals that connect If and Ca2+ clock mechanisms are uncertain and controversial, but the multifunctional Ca2+ and calmodulin-dependent protein kinase II (CaMKII) is required for physiological heart rate responses to β-adrenergic receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…BayK 8644 increased heart rate in a dose-dependent fashion over a similar dynamic range as isoproterenol, but without increasing I f , suggesting that Ca 2+ -dependent mechanisms were fully capable of generating physiological fight or flight heart rate responses. SAN cells and isolated hearts from mice with genetic CaMKII inhibition were refractory to heart rate increases and had reduced late diastolic intracellular calcium release and I NCX when treated with BayK 8644 compared to WT controls, even though Bay K increased I Ca equally in all SAN cells 34 . These findings suggested that CaMKII contributes to heart rate by a series of events that promote SR Ca 2+ release and I NCX in SAN cells.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…BayK 8644 increased heart rate in a dose-dependent fashion over a similar dynamic range as isoproterenol, but without increasing I f , suggesting that Ca 2+ -dependent mechanisms were fully capable of generating physiological fight or flight heart rate responses. SAN cells and isolated hearts from mice with genetic CaMKII inhibition were refractory to heart rate increases and had reduced late diastolic intracellular calcium release and I NCX when treated with BayK 8644 compared to WT controls, even though Bay K increased I Ca equally in all SAN cells 34 . These findings suggested that CaMKII contributes to heart rate by a series of events that promote SR Ca 2+ release and I NCX in SAN cells.…”
Section: Introductionmentioning
confidence: 95%
“…Excess Ca 2+ in diastole increases the likelihood for DADs due to the electrogenic action of NCX1. Interestingly, the pathological actions of CaMKII to favor DADs in atrial 114 and ventricular 74 myocardium mirror the physiological role of CaMKII to promote RyR2 Ca 2+ leak and increased automaticity in SA nodal pacemaker cells 33,34 . While the role of CaMKII in RYR dysfunction in heart failure is controversial and in early studies mice with genetically altered RyR, resistant to CaMKII phosphorylation, are not protected from heart failure 32 , pathological effects of CaMKII were recently shown in knock-in mice with RyR genetically modified to mimic RyR phosphorylation by CaMKII (Ser 2814 Asp) 115 .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, IP 3 -activated IP 3 R1 may directly or indirectly interact with canonical transient receptor potential channel (TRPC) channels in smooth muscle [73]. (v) Ca 2+ release from IP 3 R could activate other Ca 2+ dependent cellular mechanism or signaling pathways such as Ca 2+ -activated isoforms of adenylyl cyclase [74], Ca 2+ /calmodulin-dependent protein kinase II, both of which have been shown to play an important role in regulation of heart rate, and they are highly dependent on intracellular Ca 2+ [75].…”
Section: Evidence For a Contribution Of The Ip 3 R Signaling Pathway mentioning
confidence: 99%